Dysprosium-directed metallosupramolecular network on graphene/Ir(111). Issue 11 (12th January 2021) - Moreno, Daniel; Cirera, Borja; Parreiras, Sofia O.; Urgel, José I.; Giménez-Agulló, Nelson; Lauwaet, Koen; Gallego, José M.; Galán-Mascarós, José R.; Martínez, José I.; Ballester, Pablo; Miranda, Rodolfo; Écija, David
Abstract : On-surface design of dysprosium-directed metal-organic network on graphene/Ir(111). Abstract : The interest in exploiting the unique properties of lanthanides has led to the recent design of two-dimensional coordination networks incorporating f-block elements on metallic surfaces. In order to take this field to the next step of progression, it is necessary to electronically decouple these two-dimensional architectures from the metallic surface underneath. As a first step in this direction, we report the formation of dysprosium-directed metal–organic networks employing three-fold ligands as molecular linkers equipped with terminal carbonitrile functional groups on weakly interacting substrates such as Au(111) and graphene/Ir(111). We observe on both substrates identical quasi-hexagonal Dy–carbonitrile coordination networks based on majority five-fold nodes. Our findings provide perspectives for the formation of lanthanide coordination networks on graphene and related sp 2 materials grown on metals.